The Influence of Transformational Leadership and Work Motivation on Teacher Performance at SMA Mahawarman Bandung Regency - Abdul Jamil; Ericho Agil Nugraha (STMIK Indonesia Banda Aceh, 2026)
The main problem in this research is to determine the extent of the influence of transformational leadership and work motivation on teacher performance at SMA Mahawarman Bandung Regency, both simultaneously and partially. The purpose of this research is to identify and analyze transformational leadership, work motivation, and teacher performance, as well as the magnitude of the influence of transformational leadership and work motivation on teacher performance at SMA Mahawarman Bandung Regency, both simultaneously and partially. The method used in this research is a quantitative approach. The population in this research consists of teachers at SMA Mahawarman Bandung Regency. The sample in this research is 45 teachers. The data in this research is primary data, obtained from respondents' answers to questionnaires distributed by the author. The results of the data analysis conducted by the author show that simultaneously, transformational leadership and work motivation have a significant positive effect on teacher performance (F = 18.245; p < 0.001; R = 0.612; R² = 0.375). Partially, the standardized coefficient of transformational leadership (β = 0.287; p = 0.023) and work motivation (β = 0.198; p = 0.045) are significant. Teacher performance is influenced by transformational leadership and work motivation variables by 37.5% in a positive direction.